2022
DOI: 10.1038/s41598-022-05050-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylation analyses identifies Non-coding RNA genes dysregulated in breast tumours that metastasise to the brain

Abstract: Brain metastases comprise 40% of all metastatic tumours and breast tumours are among the tumours that most commonly metastasise to the brain, the role that epigenetic gene dysregulation plays in this process is not well understood. We carried out 450 K methylation array analysis to investigate epigenetically dysregulated genes in breast to brain metastases (BBM) compared to normal breast tissues (BN) and primary breast tumours (BP). For this, we referenced 450 K methylation data for BBM tumours prepared in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This suggests using these microRNAs as possible biomarkers to differentiate between primary brain tumors and brain metastases [ 16 ]. Another study by Pangeni et al found that many deregulated non-protein-coding genes are associated with brain metastases [ 17 ]. They found three of these genes are hypermethylated (MIR124-2, RP11-713P17.4, NUS1P3), while the other three genes, including CTD-2023M8.1, MIR3193, and MTND6P4, are found to be hypomethylated in brain metastases compared to primary brain tumors [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests using these microRNAs as possible biomarkers to differentiate between primary brain tumors and brain metastases [ 16 ]. Another study by Pangeni et al found that many deregulated non-protein-coding genes are associated with brain metastases [ 17 ]. They found three of these genes are hypermethylated (MIR124-2, RP11-713P17.4, NUS1P3), while the other three genes, including CTD-2023M8.1, MIR3193, and MTND6P4, are found to be hypomethylated in brain metastases compared to primary brain tumors [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Another study by Pangeni et al found that many deregulated non-protein-coding genes are associated with brain metastases [ 17 ]. They found three of these genes are hypermethylated (MIR124-2, RP11-713P17.4, NUS1P3), while the other three genes, including CTD-2023M8.1, MIR3193, and MTND6P4, are found to be hypomethylated in brain metastases compared to primary brain tumors [ 17 ]. This suggests that epigenetic regulation of the genes coding for ncRNAs can affect their expression, leading to altered levels and inducing tumor cell invasion, proliferation, and migration.…”
Section: Reviewmentioning
confidence: 99%
“…There was 100% concordance with the tissue status in miR124-2 and CTD-2028 M8 . However, CCDC8 showed 80%, and miR3193 had a 50% similar status [ 42 ]. Out of these genes miR124-2, CCDC8 were found to be hypermethylated, whereas miR3193 was hypomethylated.…”
Section: Introductionmentioning
confidence: 99%